The real-world safety profile of SGLT2 inhibitors among adults 75 years or older: a retrospective, pharmacovigilance study. (3rd October 2022) - Goldman, A; Fishman, B; Raschi, E; Cukierman-Yaffe, T; Dankner, R; Ben-Zvi, I; Maor, E
Abstract: Introduction: As indications for sodium-glucose co-transporter-2 (SGLT2) inhibitors treatment are expanding, more older adults become candidates for treatment. However, data regarding the treatment's safety profile in the older population are limited. Methods: A retrospective, pharmacovigilance study of the FDA's global database of safety reports (7/1/2014–6/30/2021). To assess reporting of pre-specified adverse events following SGLT2-inhibitors treatment among adults (18≥age<75) and older adults (age≥75), we performed disproportionality analysis using the reporting odds ratio (ROR). Results: Of 10, 526, 408 patients in the full database, 279, 619 eligible patients with non-insulin-dependent diabetes mellitus were identified (mean age 63.4 [SD 13.0] years, 54, 791 [19.6%] aged ≥75 years), among whom 29, 431 receiving SGLT-2 inhibitors. Compared to other non-insulin anti-diabetics, SGLT2-inhibitors were significantly associated with amputations (ROR=127.87 [95% CI: 111.31–146.90] vs ROR=74.91 [49.99–112.25]), Fournier gangrene (ROR=53.27 [44.38–63.92] vs ROR=33.33 [20.33–54.64]), diabetes ketoacidosis (ROR=39.25 [37.20–41.42] vs ROR=58.46 [49.41–69.1]), genitourinary infections (ROR=4.36 [4.12–4.61] vs ROR=5.08 [4.45–5.79]), nocturia (ROR=2.81 [2.13–3.73] vs ROR=3.51 [1.84–6.68]), and dehydration (ROR=2.22 [2.05–2.40] vs ROR=2.33 [1.93–2.81]) in both adults and older adults, respectively. The relative reporting of these safety signals was consistent between age groups (all P interaction >0.05). Acute kidney injury was associated with SGLT2-inhibitors treatment in adults (ROR=1.47 [1.40–1.54]) but not older adults (ROR=0.84 [0.72–0.98]). No new safety signals were observed in older adults. Falls, fractures, hypotension, and syncope were not associated with SGLT2-inhibitors among either adults or older adults. Conclusion: In this global post-marketing study, treatment with SGLT-2 inhibitors in older adults was associated with increased reporting of amputations, Fournier gangrene, DKA, genitourinary infections, and dehydration. Nevertheless, the relative reporting was consistent between adults and older adults, and no new safety signals were found in the older population. Funding Acknowledgement: Type of funding sources: None.